2014
DOI: 10.1007/s13669-013-0071-6
|View full text |Cite
|
Sign up to set email alerts
|

Management of Chemoresistant and Quiescent Gestational Trophoblastic Disease

Abstract: Gestational trophoblastic neoplasia (GTN) is highly chemosensitive and has a high cure rate. Since the introduction of chemotherapy, reliable measurement of human chorionic gonadotropin (hCG) levels, and individualised risk-based therapy into the management of GTN, almost all low-risk and more than 80 % of high-risk GTN cases are curable. However, approximately 25 % of high-risk GTN developed resistance to chemotherapy or relapsed after completion of initial therapy, which often necessitate salvage combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 50 publications
0
18
0
3
Order By: Relevance
“…In contrast, a diagnosis of recurrence is made when there are two elevations of hCG concentrations in the absence of pregnancy after a normal hCG result 40 . Both conditions are challenging in the treatment of GTN.…”
Section: Resistant or Recurrent Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a diagnosis of recurrence is made when there are two elevations of hCG concentrations in the absence of pregnancy after a normal hCG result 40 . Both conditions are challenging in the treatment of GTN.…”
Section: Resistant or Recurrent Diseasementioning
confidence: 99%
“…The rate of complete response to this regimen is higher among patients that develop resistance (81.8%) than in those with disease recurrence (42.9%), and the most common side effects are myelosuppression, nausea, Table 4. Salvage chemotherapy for resistant or relapsed gestational trophoblastic neoplasia 40 vomiting and hepatotoxicity 46 . With divergent results, Powles et al 47 found an overall 5-year survival of 93% for patients with recurrent disease and 43% for those with chemoresistant disease.…”
Section: Resistant or Recurrent Diseasementioning
confidence: 99%
“…HMs occur in ~1:600 pregnancies in the United Kingdom (1), with even higher rates in the Middle East, Latin America, Africa and the Far East (2–5). The majority of HMs will spontaneously regress following suction evacuation; however, 8–30% of HMs persist after evacuation and develop into gestational trophoblastic neoplasia (GTN), requiring chemotherapy (6). …”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of chemotherapy, reliable measurement of serum β human chorionic gonadotropin (β-hCG) levels and individualized risk-based therapy into the management of GTN, the majority of low-risk and 80% of high-risk GTN cases are curable (6). However, 15–25% of high-risk GTNs develop resistance to chemotherapy, or relapse following the completion of initial therapy, necessitating salvage combination chemotherapy (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation